Ageing with a learning disability: Care and support in the context of austerity. (June 2019) - Power, Andrew; Bartlett, Ruth
Abstract: Recent work in geography has begun to look at the opportunities for care from siblings, friends and neighbours alongside parents and spouses. This paper examines the daily relationships that middle to older age adults with a learning disability have with remaining kin members, friends, and neighbours, within the context of declining formal day services. Adults with learning disabilities are more likely to have different life course experiences and be living on low incomes and in poor housing than the rest of the population as they have had less opportunity to work and save money through their lives. We draw on two qualitative studies with adults with learning disabilities. Findings suggest that friend and kin networks are anything but certain, as opportunities to meet and socialise shrink, and connections with siblings do not necessarily lend themselves to support. The findings raise the possibility of a space of attenuated care to convey the increasingly limited fronts from which support can be derived. Highlights: Study examines informal care gaps in times of austerity. It focuses on middle to older age adults with learning disabilities. Findings suggest support from friends, neighbours and siblings is very uncertain. There are also retreating opportunities and spaces to meet friends and socialise. Study contributes idea of 'care desert' to geographies of care and disability.